2019
DOI: 10.1002/sctm.18-0236
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Reconditioned in Their Own Serum Exhibit Augmented Therapeutic Properties in the Setting of Acute Respiratory Distress Syndrome

Abstract: Mesenchymal stem cells (MSCs) are a promising form of therapy for acute respiratory distress syndrome (ARDS). The objective of this study was twofold: (a) to characterize cytokine expression in serum from ARDS subjects receiving MSCs and (b) to determine MSC function following “preconditioning” with ARDS serum. In phase I, serum from three cohorts of animals (uninjured [no ARDS, n = 4], injured untreated [n = 5], and injured treated with approximately 6 million per kilogram MSCs [n = 7]) was analyzed for expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
(47 reference statements)
0
23
0
Order By: Relevance
“…Intravenous injection of IL‐1Ra‐producing MSCs completely attenuated lung inflammation in mice by suppressing the production of TNF‐α, IL‐1α, and IL‐1β in alveolar macrophages resulting in alleviated influx of circulating neutrophils and lymphocytes in BLM‐injured lungs . The highest production of IL‐1Ra by lung‐infiltrated MSCs was observed 72 hr after lung injury and was mainly triggered by IL‐6, released from lung‐infiltrated neutrophils and alveolar macrophages . Importantly, as revealed by Xu and colleagues, MSC‐derived IL‐1Ra creates “positive autocrine loop” in population of lung‐infiltrated MSCs by promoting their expansion and capacity for neovascularization, bacterial clearance, and immunosuppression .…”
Section: Il‐1ra‐expressing Mscs As a New Therapeutic Agent In The Celmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenous injection of IL‐1Ra‐producing MSCs completely attenuated lung inflammation in mice by suppressing the production of TNF‐α, IL‐1α, and IL‐1β in alveolar macrophages resulting in alleviated influx of circulating neutrophils and lymphocytes in BLM‐injured lungs . The highest production of IL‐1Ra by lung‐infiltrated MSCs was observed 72 hr after lung injury and was mainly triggered by IL‐6, released from lung‐infiltrated neutrophils and alveolar macrophages . Importantly, as revealed by Xu and colleagues, MSC‐derived IL‐1Ra creates “positive autocrine loop” in population of lung‐infiltrated MSCs by promoting their expansion and capacity for neovascularization, bacterial clearance, and immunosuppression .…”
Section: Il‐1ra‐expressing Mscs As a New Therapeutic Agent In The Celmentioning
confidence: 99%
“…54 The highest production of IL-1Ra by lunginfiltrated MSCs was observed 72 hr after lung injury and was mainly triggered by IL-6, released from lunginfiltrated neutrophils and alveolar macrophages. 53,56,57 Importantly, as revealed by Xu and colleagues, MSCderived IL-1Ra creates "positive autocrine loop" in population of lung-infiltrated MSCs by promoting their expansion and capacity for neovascularization, bacterial clearance, and immunosuppression. 53,55 Under the influence of IL-1Ra, MSCs upregulate the expression of vascular endothelial growth factor (VEGF) that prevents the apoptosis of endothelial cells, induces neovascularization, and promotes regeneration of injured alveolar Type II epithelial cells.…”
Section: Il-1ra-expressing Mscs As a New Therapeutic Agent In The Cmentioning
confidence: 99%
“…1 Notably, it has been proved that MSC-released cytokines can potently inhibit neutrophil intravasation and enhance the differentiation of macrophages. 5,6 Moreover, these MSC-released EVs can deliver microRNA, mRNA, DNA, proteins, and metabolites into host cells in specific injuries of the lung to promote lung repair as well as regeneration and restore lung function. 1 As the continuing epidemic threat of SARS-CoV-2 to global health and the fast-growing number of fatalities, advancing new therapeutic development becomes central or primary to minimize the death and sequelae from SARS-CoV-2 infection.…”
Section: Mesenchymal Stem Cells As a Potential Treatment For Criticalmentioning
confidence: 99%
“…1) (68). Notably, it has been shown that cytokines released by MSCs may potently inhibit neutrophil intravasation and enhance the differentiation of macrophages (69,70).…”
Section: Mscsmentioning
confidence: 99%